2013
DOI: 10.1055/s-0033-1363093
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Physiological and Biochemical Parameters and the Autonomic Nervous Systems of Children with Breath-Holding Spells

Abstract: Autonomic dysfunction existed in the children with BHS, but no correlation was found between BHS and deficiencies of iron, vitamin D, or vitamin B12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
10
2
1
Order By: Relevance
“…Between the breath holders and non‐breath holders in our study, no significant difference in the number of cases of iron deficiency anaemia was found. However, there are conflicting reports about this relationship …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Between the breath holders and non‐breath holders in our study, no significant difference in the number of cases of iron deficiency anaemia was found. However, there are conflicting reports about this relationship …”
Section: Discussionmentioning
confidence: 99%
“…The mechanism and causes of BHS are not clearly understood. Prior studies have reported relationships between BHS and iron deficiency anaemia, 4 autonomic dysregulation 6 and cardiac causes. 20 Between the breath holders and non-breath holders in our study, no significant difference in the number of cases of iron deficiency anaemia was found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La función vagal, evaluada mediante diversos test neurofisiológicos, como el reflejo oculocardíaco, el test de pilocarpina y parámetros de variabilidad de la frecuencia cardíaca en Holter de 24 h, han evidenciado una sobre-reactividad, más que sobreactividad vagal [14][15][16] . Para antagonizar la sobre-reactividad vagal y prevenir la AE se han usado drogas anticolinérgicas como atropina, escopolamina y glicopirrolate 17,18 .…”
Section: Discussionunclassified